Legal Challenges of Consumer Protection in Cross-Border E-Commerce: Towards Global Standardization - Caesaria, Dhini Rachmadhina (Fakultas Ilmu Kesehatan Universitas Gresik, 2024)
This research aims to identify the legal challenges faced in consumer protection in cross-border e-commerce transactions and explore strategies towards global standardization. The research method used was a qualitative approach with document studies and comparative analysis of consumer protection regulations in various jurisdictions, including the European Union, the United States, and Southeast Asia. Data was collected from legislation, consumer agency reports, and the latest academic literature, and then analyzed using comparative-legal methods to identify gaps in international regulations and best practices. The results of the study show significant differences in consumer protection mechanisms, dispute resolution procedures, and the implementation of cross-border consumer rights. This poses legal risks for consumers and businesses, including platform liability issues, online fraud, and limited legal access for international consumers. The study concludes that the harmonization of international regulations through flexible global standards and cross-border dispute resolution mechanisms is key to improving consumer protection. The implications of this study include recommendations for policymakers to formulate consistent regulations, support international cooperation between regulators, and for e-commerce businesses to implement transparent and accountable practices in cross-border operations.